Análisis de la situación de los barrios Inmaculada Concepción, Fátima y Arroyo Porá frente fenómeno de inundaciones urbanas (Journal on studies and research of academic knowledge, 2018)
The present work was carried out with the objective of analyzing the situation of the Immaculate Conception, Fatima and Arroyo Porá neighborhoods; For this, the characteristics of each area were analyzed, taking into account data provided by the Yacyretá Binational Entity and the Directorate of Meteorology and Hydrology of Paraguay, in addition 827 surveys were applied to housing in order to know the economic, social, physical and educational situation or knowledge The results showed that the neighborhoods have a 15% flood history for the Immaculate neighborhood, the Fatima neighborhood at 39% and the Arroyo Porá neighborhood at 17%. The average rainfall of the Mbói Caé basin is 1700 to 1800 mm and the soils are classified in class 2, 3 and 4.
Keywords: neighborhoods; urban floods; precipitation